2019
DOI: 10.1108/hff-07-2018-0349
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation of free convection’s hydrothermal aspects in a finned/multi-pipe cavity filled with CuO-water nanofluid

Abstract: Purpose This paper aims to investigate the natural convection fluid flow and heat transfer in a finned/multi-pipe cavity. Design/methodology/approach The cavity is filled with the CuO-water nanofluid. The Koo–Kleinstreuer–Li model is used to estimate the dynamic viscosity and consider Brownian motion. On the other hand, the effect of the shapes of nanoparticles on the thermal conductivity and related heat transfer rate is presented. Findings In the present investigation, the governing parameters are Raylei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Although the subject of MHD non-Newtonian fluid flow and heat transfer in a pipe and coaxial cylinders has been studied (Rahimi et al, 2019;Ulker et al, 2018;Saberinejad et al, 2018;Ban et al, 2018;Malik et al, 2016), concerning the aforementioned research review, little research conducted for solving this kind of problem considering a variable radius ratio, the radial magnetic field, the viscous dissipationand the convection heat transfer boundary conditions. Furthermore, though approximate analytical solutions do not exactly satisfy the problem solution, acceptable results can be obtained by analyzing them.…”
Section: Hff 313mentioning
confidence: 99%
“…Although the subject of MHD non-Newtonian fluid flow and heat transfer in a pipe and coaxial cylinders has been studied (Rahimi et al, 2019;Ulker et al, 2018;Saberinejad et al, 2018;Ban et al, 2018;Malik et al, 2016), concerning the aforementioned research review, little research conducted for solving this kind of problem considering a variable radius ratio, the radial magnetic field, the viscous dissipationand the convection heat transfer boundary conditions. Furthermore, though approximate analytical solutions do not exactly satisfy the problem solution, acceptable results can be obtained by analyzing them.…”
Section: Hff 313mentioning
confidence: 99%
“…It was found that the obstacle and the magnetic effects collaborate in controlling the flow. Rahimi et al (2019) considered a multipipe enclosure containing Cu-nanofluid at various nanoparticle concentrations. The authors mentioned that the hydrothermal properties are very sensitive to the concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, the natural convection can be found in the solar collector, heat exchangers, cooling of electronic devices, nuclear power plants, geothermal systems, HVAC, etc. (Rahimi et al, 2019a(Rahimi et al, , 2019b(Rahimi et al, , 2019c(Rahimi et al, , 2019dHooshmand et al, 2019;Al-Rashed Abdullah et al, 2019;KhakRah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The results illustrated the great impact of surface radiation on thermal rate and flow field during natural convection. Rahimi et al (2019aRahimi et al ( , 2019bRahimi et al ( , 2019cRahimi et al ( , 2019d) provided a comprehensive review paper which covers the recent works on natural convection in different types of configurations, numerical methods and operating fluids. A great variety of geometries included with different physical and thermal boundary conditions, heat sources and fluid/ nanofluid media are analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation